2001
DOI: 10.1346/ccmn.2001.0490408
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl-Stretching Bands in Curve-Fitted Micro-Raman, Photoacoustic and Transmission Infrared Spectra of Dickite from St. Claire, Pennsylvania

Abstract: Abstract--The OH-stretching region in curve-fitted micro-Raman, photoacoustic and transmission IR spectra of St. Claire dickite was investigated. Polarized Raman spectra recorded from the (001) and (010) faces of the dickite crystal displayed six prominent OH bands. The relative intensities depend strongly on both the orientation of the crystallographic axes and the direction of the electric vector of the laser beam. Four out-of-plane vibrations, AA, Az, CA and Ca, at --3710, 3706, 3654 and 3643 cm J respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It may be used as excellent filler, especially barrier filler because of its layer structure. In recent years, main researches about dickite were paid to several aspects as followed: hydroxyl‐stretching mode,14–17 thermal behavior,18–21 adsorption,22–25 and intercalation18, 20, 21, 26 of organic molecule. In addition, the formation,27, 28 distribution,29–31 and mineralogy character32 of dickite were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…It may be used as excellent filler, especially barrier filler because of its layer structure. In recent years, main researches about dickite were paid to several aspects as followed: hydroxyl‐stretching mode,14–17 thermal behavior,18–21 adsorption,22–25 and intercalation18, 20, 21, 26 of organic molecule. In addition, the formation,27, 28 distribution,29–31 and mineralogy character32 of dickite were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…'Chromeleon ' [Dionex Corporation, 2001], 'PyMS' [O'Callaghan et al, 2012] and 'AMDIS' [Nair et al, 2013]), although research has shown that the larger amount of available processing options can often be misleading resulting in inadequately processed signals [e.g. Shoval, 2001;Fagan, 2011;de la Mata et al, 2012;Zhou, 2013;Giovanelli, 2014]. For more targeted data processing, custom made data processing has been developed that based on assessment of the nature of signal and noise [e.g.…”
Section: Noise Reduction/removal Involving Software Adjustmentsmentioning
confidence: 99%
“…For more targeted data processing, custom made data processing has been developed that based on assessment of the nature of signal and noise [e.g. Shoval, 2001;Fagan, 2011;de la Mata et al, 2012;Zhou, 2013;Giovanelli, 2014]. These custom made tools make use of signal filtering to reduce the effect of background noise on the analyte signal.…”
Section: Noise Reduction/removal Involving Software Adjustmentsmentioning
confidence: 99%